PD-1/PD-L1 expression in extra-medullary lesions of multiple myeloma. (October 2016) - Crescenzi, Anna; Annibali, Ombretta; Bianchi, Antonella; Pagano, Anastasia; Donati, Michele; Grifoni, Alba; Avvisati, Giuseppe
Highlights: PD-L1+ immunohistochemical reaction was observed in the 33% of the EMP cases. All cases showed presence of PD-1+ infiltrating lymphocytes among neoplastic cells. Our results identify PD-1/PD-L1 axis in EMP lesions both at diagnosis and relapse. Abstract: Multiple myeloma patients may develop extraosseous involvement in the course of the disease making prognosis very poor and new drugs clearly needed. The PD-1/PD-L1 axis has emerged as a master immune checkpoint in antitumor responses and recent studies investigated the role of PD-L1 in multiple myeloma cells; no data however are still available about PD-L1 expression in extramedullary localizations. We demonstrate PD-L1 expression in 4/12 cases of extraosseous myeloma suggesting that these lesions represent a specialized microenvironment. We found presence of PD-1+ infiltrating lymphocytes in all observed cases supporting the relevance of PD-1/PD-L1 checkpoint in extramedullary myeloma. We also investigated the correlation in PD1/PD-L1 staining between marrow staining and EMP lesions.